AGRI‐FOOD AND BIO‐BASED ANALYSIS IN THE SPANISH ECONOMY USING A KEY SECTOR APPROACH. Issue 2 (27th March 2014) - Cardenete, Manuel Alejandro; Boulanger, Pierre; Del Carmen Delgado, María; Ferrari, Emanuele; M'Barek, Robert
<x xml:space="preserve">Abstract</x> The objective of this paper is to develop a coherent approach to describe the agri‐food and other bio‐based accounts in the European Union. The paper presents a case study of Spain based on a Social Accounting Matrix with a highly disaggregated agricultural account for the year 2000. The analysis of multipliers allows identifying backward and forward linkages, key sectors, and employment multipliers of the Spanish agri‐food and other bio‐based accounts. This analysis helps us to better understand the extended agri‐food account's economic linkages. No primary agricultural account emerges as key for the Spanish economy, while the production of (renewable) energy appears the only key sector related to agri‐food and other bio‐based accounts. Livestock and related bio‐based products present the highest backward linkages, that is, they have significant diffusion effects of activity to the whole economy.